Benefits and shortcomings of non-destructive benthic imagery for monitoring hard-bottom habitats. Issue 1 (15th August 2017) - Beisiegel, Kolja; Darr, Alexander; Gogina, Mayya; Zettler, Michael L.
Abstract: Hard-bottom habitats with complex topography and fragile epibenthic communities are still not adequately considered in benthic monitoring programs, despite their potential ecological importance. While indicators of ecosystem health are defined by major EU directives, methods commonly used to measure them are deficient in quantification of biota on hard surfaces. We address the suitability of seafloor imaging for monitoring activities. We compared the ability of high-resolution imagery and physical sampling methods (grab, dredge, SCUBA-diving) to detect taxonomic and functional components of epibenthos. Results reveal that (1) with minimal habitat disturbance on large spatial scales, imagery provides valuable, cost-effective assessment of rocky reef habitat features and community structure, (2) despite poor taxonomic resolution, image-derived data for habitat-forming taxa might be sufficient to infer richness of small sessile and mobile fauna, (3) physical collections are necessary to develop a robust record of species richness, including species-level taxonomic identifications, and to establish a baseline. Highlights: Epibenthic reef communities non-destructively sampled with towed camera platform Consistent comparison with physical collection data on family level Overall low taxonomic resolution but habitat-forming key taxa was detected. Image-derived data might be sufficient to infer richness of small epifauna. Suggestions for a cost-efficient monitoring over large spatial scales